Postoperative outcomes of resectable periampullary cancer accompanied by obstructive jaundice with and without preoperative endoscopic biliary drainage - Pattarapuntakul, Tanawat; Charoenrit, Tummarong; Netinatsunton, Nisa; Yaowmaneerat, Thanapon; Pitakteerabundit, Thakerng; Ovartlarnporn, Bancha; Attasaranya, Siriboon; Wong, Thanawin; Chamroonkul, Naichaya; Sripongpun, Pimsiri (Frontiers in Oncology, 2022)
Preoperative biliary drainage (PBD) is useful in resectable periampullary cancer with obstructive jaundice. Whether it is better than direct surgery (DS) in terms of postoperative complications and mortality is controversial. Postoperative outcomes might be affected by high serum bilirubin level, recent cholangitis, comorbid disease, and prolonged waiting duration for surgery. We aimed to compare these parameters of clinical outcomes between the PBD and DS groups. Methods: All cases of successful pancreaticoduodenectomy(PD) in patients with periampullary cancer with obstructive jaundice performed between January 2016 and January 2021 were retrospectively reviewed. Endoscopic PBD was performed; data pertaining to serum bilirubin level, stent type, procedural technique, and duration before surgery were obtained. The incidence of postoperative complications and survival rate were compared between the PBD and DS group. Results: A total of 104 patients (PBD, n = 58; DS, n = 46) underwent curative PD. The mean age was 63.8 ± 10 years and 53 (51%) were male. The Eastern Cooperative Oncology Group status, presence of comorbid disease, and initial laboratory results were not significantly different between the two groups. The incidence of postoperative complications was 58.6% in the PBD group while 73.9% in the DS group (relative risk [RR] 1.26, 95% confidence interval [CI] 0.92, 1.73, p=0.155) and the difference was not significant except in bile leakage (RR 8.83, 95% CI 0.68, 3.94, p = 0.021) and intraoperative bleeding (RR 3.97, 95% CI 0.88, 17.85, p = 0.049) which were higher in the DS group. The one-year survival rate was slightly less in the DS group but the difference was not statistically significant. The factors associated with overall mortality were low glomerular ejection fraction (< 70 mL/min/1.73m2), preoperative total bilirubin > 14.6 mg/dL and intraoperative bleeding. Conclusions: PBD in resectable malignant distal biliary obstruction was associated postoperative morbidity and mortality similar to that associated with DS, but may be of benefit in terms of lower risk of intraoperative bleeding and bile leakage.